CONDUCTOR’S ACTIVITY OF LEV TURKEVYCH IN THE CONTEXT OF THE UKRAINIAN DIASPORA MUSIC CULTURE - Karas, G. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In this article, we have elucidated the conductor’s activity of Lev Turkevych in the context of development of the Ukrainian Diaspora music culture after World War II on the territory of Europe, USA and Canada. Especially distinguished is the conductor’s activity with choirs «Vatra» (Aust-ria), «Prometei» and the choir of the church of Mother of Perpetual Help from Toronto (Canada).